The Deradicalization of Islamic Boarding School in Indonesia: Study About the Prevention of Radicalism and Terrorism Movement in Indonesia - Endrizal, Endrizal; Suharti, Suharti (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2023)
This research is about the deradicalization issue at Islamic boarding schools in Indonesia. The object of research is the deradicalization process in Islamic boarding schools. By using a political sociology approach, the research tries to capture the religious radicalism phenomena which are not fully the religious ideology indication but it is also social political tendency. This research is guided by social theories such as radical theory and deradicalization theory. The research method used is qualitative. Collecting data using interviews, observations, documentation and focused discussions (Focus Group Discussion). Data analysis was carried out by means of content analysis, discourse analysis and narrative analysis. Finding of the research is the radicalism action is begun from unsatisfying radical groups toward government, both in terms of economy, law, and politics. The increase of radical groups is influenced by religious doctrine taught by educational institutions affiliated with radical groups in other places. Deradicalisation is done through educational institutions and the roles of religious and state leaders. The roles of priest, curriculum and local community also have big roles in the deradicalization effort of Islamic boarding schools in Indonesia. Penelitian ini membahas tentang isu deradikalisasi di pondok pesantren di Indonesia. Objek penelitian adalah proses deradikalisasi di pondok pesantren. Dengan menggunakan pendekatan sosiologi politik, penelitian ini mencoba menangkap fenomena radikalisme agama yang tidak sepenuhnya merupakan indikasi ideologi keagamaan tetapi juga merupakan kecenderungan sosial politik. Penelitian ini berpedoman pada teori-teori sosial seperti teori radikal dan teori deradikalisasi. Metode penelitian yang digunakan adalah kualitatif. Pengumpulan data menggunakan wawancara, observasi, dokumentasi dan diskusi terfokus (Fokus group Discussion. Analisis data dilakukan dengan cara analisis konten, analisis wacana dan analisis naratif. Temuan penelitian ini adalah aksi radikalisme berawal dari ketidakpuasan kelompok radikal terhadap pemerintah, baik dari segi ekonomi, hukum, maupun politik. Meningkatnya kelompok radikal dipengaruhi oleh doktrin agama yang diajarkan oleh lembaga pendidikan yang berafiliasi dengan kelompok radikal di tempat lain. Deradikalisasi dilakukan melalui lembaga pendidikan dan peran pemimpin agama dan negara. Peran imam, kurikulum dan masyarakat lokal juga memiliki peran besar dalam upaya deradikalisasi pesantren di Indonesia.